Wall Heat Transfer Analysis of Internal Combustion Engine with Free Piston Linear Motion - A. Said, Mior; K. Mun, L; R. A. Aziz, A; ., . (International Journal of Engineering and Technology, 2018)
The manuscript should contain an abstract. The abstract should be self-contained and citation-free and should not exceed 200 words. The abstract should state the purpose, approach, results and conclusions of the work.Â The author should assume that the reader has some knowledge of the subject but has not read the paper. Thus, the abstract should be intelligible and complete in it-self (no numerical references); it should not cite figures, tables, or sections of the paper. The abstract should be written using third person instead of first person.Â Intensive researches are being carried out on the main power generator for free piston linear generator(FPLG) by both the academic and industrial research group due to its potential as a high fuel efficiency and low emission engine. The linear generator, which is a coil and a translator positioned to move linearly back and forth relative to each other. The study investigates the heat transfer data of internal combustion engine with free piston linear motion profile and compared with the conventional reciprocating engine for one cycle motion only. Engine simulation software GT-Power is employed which utilize the 1-D thermodynamic modeling. All parameters for both free-piston engine are set-up to be the same except for the piston motion profile and the injection timing. Both conventional and free piston engine models are built, simulation settings are set up, and simulations are launched in GT-ISE.Â Once simulation is done, results are viewed in GT-POST, the data collected was analysed and compared to investigate the dictinct effect of piston motion to heat transfer profile and data. The overall trend shows that free piston engine have a lower heat transfer rate throughout majority of the cycle. This finding agrees that due to less time of piston near top dead centre area, heat transfer losses to the wall per cycle are reduced. The heat transfer profile of the free piston also shown distinct feature compared to conventional with rapid increase and decrease of heat transfer rate, followed by a secondary peak of gradual decline of the profile.Â Â